Correlation between Low Birth Weight and Social-Emotional Development in Toddlers - Nourma Andini, Aisyah; Ira Rahmawati; Afdi Septiono, Eka (Nursing and Health Sciences Journal (NHSJ), 2023)
Low birth weight can be one of the factors that can affect the social-emotional development of toddlers. Previous research has indicated that LBW toddlers are more likely to have issues with their social-emotional development. Since this developmental domain influences cognitive function, motor function, and linguistic abilities, it may have an effect on children's performance in the future. This study aims to determine whether the history of low birth weight is related to the social-emotional development of toddlers in the UPT Puskesmas Kalisat Working Area, Jember. Cross-sectional study with the quantitative analysis used in this study. The number of samples is 125 respondents using a multistage cluster random sampling technique. Data was collected using the MCH (Maternal and Child Health) book to find out the history of birth weight and the PPSC (Pediatric Preschool Symptom Checklist) questionnaire. The results showed that 66 children (52.8%) did not have a history of LBW. The social-emotional development of toddlers is mostly not at risk of experiencing social-emotional development disorders, with a total of 69 toddlers (57.2%). Chi-square test analysis obtained a p-value of 0.147 > 0.05, which means that there is no significant relationship between LBW history and social-emotional development in toddlers. However, it is important to underline that social-emotional development is influenced by various factors. This study shows that factors of nutritional status, age of mother/caregiver, and educational status of mother/caregiver statistically affect social-emotional development (p<0.05).